Evaluation of biofilm formation in the homozygous and heterozygous strains of vaginal Candida albicans isolates - Keyvan Pakshir; Sahar Sheykhi; Kamiar Zomorodian; Hasti Nouraei; Zahra Zareshahrabadi (Mazandaran University of Medical Sciences, 2019)
Background and Purpose: Candida albicans is one of the most opportunistic yeasts around the world. This species has two heterozygous and homozygous strains at hyphal wall protein 1 (hwp1) gene locus. A simple method for the discrimination of these two strains is the amplification of HWP1 gene. Regarding this, the aim of this study was to discriminate C. albicans heterozygous and homozygous strains via the amplification of hwp1 gene and evaluation of biofilm formation between the strains. Materials and Methods: A total of 60 homozygous (n=30) and heterozygous (n=30) strains were discriminated among 126 C. albicans vaginal isolates by the amplification of HWP1 gene, using specific primers. The evaluation of biofilm formation was accomplished using the visual method. Results: According to the results, the homozygous and heterozygous strains produced one and two DNA fragments, respectively. The frequency of homozygous strains among the C. albicans vaginal isolates was 76.2%. Biofilm formation activity in the heterozygous strains was more than that in the homozygous strains. However, statistical analysis showed no significant difference between the strains in terms of biofilm formation. Conclusion: As the findings indicated, the frequency of the heterozygous strains in C. albicans was lower than that of the homozygous strains. Both of the strains could form biofilm in the different ranges of severity. High activity of biofilm formation in heterozygous strains may set the ground for its pathogenicity.